Analisis Penerapan Sistem Akuntansi Manajemen terhadap Pengendaian Kualitas Produk pada Benings Clinic Medan - Dimas Sanjaya; Rahmat Daim Hrp (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The development of the current management accounting system is very rapid. company managers need a management information system to implement the functions of planning, controlling, and decision making. The management accounting system is a system that collects operational and financial data, processes, stores and reports to users, namely employees, managers, and executives. The purpose of this study is to analyze the management accounting system for product quality control at Benings Clinic Medan. The method used is descriptive qualitative. The results of the implementation of the management accounting system at Benings Clinic Medan have shown its role as a tool in controlling product quality and can help managers be better prepared to handle company problems and control product quality walk.